Co-existence effect of copper oxide nanoparticles and ciprofloxacin on simultaneous nitrification, endogenous denitrification, and phosphorus removal by aerobic granular sludge. (January 2023) - Li, Yu-Qi; Zhao, Bai-Hang; Chen, Xiao-Tang; Zhang, Yu-Qing; Yang, Hai-Shan
Abstract: Nanoparticles and antibiotics are toxic to humans and ecosystems, and they inevitably coexist in the wastewater treatment plants. Hence, the co-existence effects and stress mechanism of copper (II) oxide nanoparticles (CuO NPs) and ciprofloxacin (CIP) on simultaneous nitrification, endogenous denitrification and phosphorus removal (SNEDPR) by aerobic granular sludge (AGS) were investigated here. The co-existence stress of 5 mg/L CuO NPs and 5 mg/L CIP resulted in the synergistic inhibitory effect on nutrient removal. Transformation inhibition mechanisms of carbon (C), nitrogen (N) and phosphorus (P) with CuO NPs and CIP addition were time-dependent. Furthermore, the long-term stress mainly inhibited PO4 3- -P removal by inhibiting phosphorus release process, while short-term stress mainly inhibited phosphorus uptake process. The synergistic inhibitory effect of CuO NPs and CIP may be due to the changes of physicochemical characteristics under the co-existence of CuO NPs and CIP. This further altered the sludge characteristics, microbial community structure and functional metabolic pathways under the long-term stress. Resistance genes analysis exhibited that the co-existence stress of CuO NPs and CIP induced the amplification of qnrA (2.38 folds), qnrB (4.70 folds) and intI1 (3.41 folds) compared with the control group. Graphical abstract: Image 1 Highlights: CuO NPs and CIP performed synergistic inhibitory effects on SNEDPR-AGS performance. SNEDPR was damaged under the long-term co-existence stress of CuO NPs and CIP. Inhibition mechanism of C, N and P transformation was related to the stress time. Co-existence of CuO NPs and CIP synergistically induced qnrB and intI1 .